The Implementation of Integrity Values to Foster Anti-Corruption Attitudes in Elementary School Students - Heryanto, Debi; Susanti, Atika; Darmansyah, Ady (IJECA (International Journal of Education and Curriculum Application), 2023)
Anti-corruption education plays a crucial role in addressing the issue of corruption. The rise in corruption cases showcased on various social media platforms indicates the urgency of preventing and eliminating its adverse effects on the nation's economy, core values, and state ideology. This research aims to describe the implementation of Integrity Values to Foster Anti-Corruption Attitudes in Elementary School Students. The research methodology used is a qualitative descriptive method. The subjects in the research include both teachers and students. Specifically, the study encompassed three teachers and nine students in the 4th grade. Research instruments used observation guidelines, interview guides, and documentation. Data were collected through observation, interviews, and documentation. Data analysis was conducted through several steps, including data collection, data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, this research examined four dimensions: credibility, transferability, dependability, and confirmability. The results of this research indicate that the implementation of integrity values in the effort to foster anti-corruption attitudes among students at Elementary School has been carried out through various activities, including: (1) The "Honesty Canteen," where students are provided with the opportunity to interact with integrity in a real-life context, (2) The correction of homework assignments in the classroom, which encourages students to complete tasks honestly and accurately, (3) The teaching of Civic Education at the elementary school level, (4) The enforcement of rules regarding school attendance, guiding on school discipline. Based on the research findings, it can be deduced that the implementation of integrity values aimed at fostering anti-corruption attitudes at Elementary School has achieved success, especially within the context of the national curriculum and various student-engaging activities within the school. This underscores the school's commendable efforts in instilling anti-corruption values among elementary school students.